Information and Communication Technology (ICT) Skills: Are They Important For Prospective Mathematics Teachers? - Yulianti, Putri; Handican, Rhomiy (Insitut Agama Islam Negeri Kerinci, 2023)
At this time the demands of education are increasingly modern where teachers are required to be able to adapt to the development of increasingly sophisticated technology. The ability in the field of Information and Technology (ICT) is an important thing that must be mastered to be able to produce mathematics teachers who are able to answer the challenges of the 21st century in the field of technology integration in learning. The purpose of this research is to see the views of Tadris Mathematics students on the importance of ICT skills to be mastered by prospective mathematics teachers in making ICT-based learning media. This research is a descriptive qualitative research type survey conducted at the Kerinci State Islamic Institute by distributing questionnaires to 67 students in the mathematics tadris department from various levels. From the research conducted obtained 59.5% of students can make ICT-based learning media, 73% of students have made learning media, 72.4% of students stated that they wanted to deepen their ability to utilize ICT capabilities to make learning media. Researchers can conclude from the findings that the knowledge of Information and Comunication Tcnology is very important for students as prospective mathematics education teachers who will face the technological revolution that is increasingly developing at this time.